Desenvolvimento de sistema multivitamínico encapsulado em lipossomas para saúde da pele - Novicki, Luiza Hauser (2022)
Skin aging is a biological process that is characterized by cellular changes, resulting in the loss of its properties and tissue replication becomes less efficient. There are some agents that help prevent skin aging, such as antioxidants that fight the action of free radicals. However, the skin works as a barrier and for these assets to be able to perform their function they need to overcome it. Thus, the purpose of this work was to develop a formulation containing vitamins C, D and E encapsulated in liposomal vesicles for better penetration into the skin. The challenge of placing vitamins with different levels of solubility began with experiments on the encapsulation of each vitamin in liposomal vesicles as well as their characterization. Different encapsulation methods were performed to provide the best encapsulation efficiency, and the one that offered the best result was the sonication method with 2% of T80. The new final formulation was able to encapsulate 53.69% of vitamin C (present in the aqueous core of the liposomes), 99.09% of vitamin D and 100% of vitamin E (present in the lipid bilayer). The release tests were performed in Franz cell and it was possible to observe that the vitamins encapsulated in liposomes took longer to start the release process and remained releasing for a longer time compared to free vitamins. The characterization methods used in the work were ultraviolet visible spectroscopy (UV-Vis), dynamic light scattering (DLS) and high-performance liquid chromatography (HPLC).